Rivaroxaban versus Aspirin in Prevention of Venous Thromboembolism: A Meta-Analysis of 9 Randomized Controlled Trials comprising 7,656 Patients - Xie, Jian; Jiang, Mingyang; Lin, Yunni; Deng, Huachu; Xie, Xiaoyong; Li, Lang (Thrombosis and Haemostasis, 2019)
Aim This article evaluates the preventive effects of rivaroxaban versus aspirin on venous thromboembolism (VTE) through meta-analysis of recent randomized controlled trials (RCTs).Methods RCTs were retrieved from medical literature databases. Risk ratios (RRs) and 95% confidence intervals (CIs) were calculated to compare the primary and safety endpoints.Results In total, 9 trials (11 trial comparisons) were retrieved which contained 7,656 patients. Among these patients, 4,383 patients (57.2%) received rivaroxaban, whereas 3,273 patients (42.8%) received aspirin. Compared with aspirin, rivaroxaban significantly reduced VTE (1.3% vs. 3.5%) (RR: 0.36, 95% CI, 0.26–0.48, I2 = 27.9%), but significantly increased nonmajor bleeding (11.5% vs. 7.5%) (RR: 1.28, 95% CI, 1.13–1.44, I2 = 38.6%). There were no significant differences in the all-cause mortality (0.3% vs. 0.3%) (RR: 0.75, 95% CI, 0.35–1.61, I2 = 32.0%) and major bleeding (0.3% vs. 0.4%) (RR: 0.81, 95% CI, 0.42–1.55, I2 = 33.7%) between the two groups.Conclusion This meta-analysis indicated that rivaroxaban can significantly reduce the incidence of VTE when compared with aspirin. The preventive effect of rivaroxaban on VTE was more potent than that of aspirin. However, rivaroxaban had some negative side effects to patients such as nonmajor bleeding compared to aspirin.
Keywords: rivaroxaban; aspirin; venous thromboembolism; meta-analysis.